Once upon a time : using stories in the language classroom - Morgan, John, 1944-2004 (Cambridge University Press, 1983)
Stories can provide a highly motivating, engaging and realistic source of genuine language interaction in the classroom. They are 'living language' in which the teacher (or student storyteller) becomes the source of language, and the listeners are actively involved in understanding. The authors argue from experience that almost everyone can tell stories convincingly, especially given an outline to work from. A very wide range of these outlines, from many cultures and sources, are provided. These can be used by the teacher as a resource for a variety of activities for students from beginner to advanced levels, including listening comprehension, grammar practice, oral production and fluency practice, but above all for exposure to real spoken language.